Glucose derivative induced vasculopathy in children on chronic peritoneal dialysis - Bartosova, Maria; Zhang, Conghui; Schäfer, Betti; Herzog, Rebecca; Riedinger, David; Damgov, Ivan; Levai, Eszter; Marinovic, Iva; Eckert, Christoph; Romero, Philipp; Sallay, Peter; Ujszaszi, Akos; et al. (Circulation research, 2021)
Download figureDownload PowerPoint